The Philosophical and Social Conditioning of Sustainable Development - Hull, Zbigniew (Problemy Ekorozwoju, 2008)
The starting point for any considerations is the assumption that the sustainable development concept ushered in by decisions of the 1992 Earth Summit in Rio de Janeiro is indeed a real social process. The course and pace of the process in turn depend on specific conditions arising which may be conducive to (or even stimulate) its development, or else slow down or even stop it. In the further part of the article I distinguish between social and philosophical conditioning of sustainable development and specify in more detail the accepted ways in which these conditions are understood, as well as seeking to take stock of and evaluate these from the point of view of positive or negative influences on the pace of the process. The article concludes with a conviction that negative influences are at present dominant, these serving to block or stop the sustainable development process.